[Em]Powering Change: Readapting and reimagining the formerAthlone Power Station, Cape Town - Liebrich, Michael (University of the Witwatersrand, Johannesburg, 2024)
Spaces of racial segregation and division are abundant in South Africa’s apartheid era urban planning. Greenbelts envisioned under the Garden City Movement to provide connection to the natural environment instead became spaces to divide residents of different ethnic groups. These spaces persist until today, their large footprints remaining as buffer spaces between race and class. One such space divides the Garden Cities of Pinelands; an affluent, predominantly white neighbourhood, and Langa; the oldest native township in Cape Town. Lack of funding, poor service provision, and historical injustices have resulted in Langa being stripped of the bucolic veneer of the Garden City, retaining only its highly controlling and ordered scheme underneath. To the South lies Athlone, a predominantly coloured neighbourhood further separated by major arterial roads. This in-between space holds the now decommissioned Athlone Power Station. For over two decades,the power station has sat idly between these three neighbourhood, its towering industrial presence dwarfing the surrounding residential contexts. The station is a place of historical injustice, of social and environmental toxicity. On the other hand, it is a site of imbued memory, of community identity, acting as a beacon for these surrounding areas. Transforming the site from a closed off space of segregation into one of homogeneity and collective memories can start bridging these historic divides. The adaptive reuse of the site into a space for people allows for life to be brought into this industrial wasteland, creating social bonds while extending the life of an architectural icon. The site is envisioned to become a form of a palimpsest, an overlay of different memories, of current activities, and of forward thinking innovation and creativity
A research report submitted in fulfillment of the requirements for the Master of Architecture, In the Faculty of Engineering and the Built Environment , School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Adaptive reuse; social cohesion; SDG-9: Industry, innovation and infrastructure; SDG-7: Affordable and clean energy